Chromosome numbers for the Italian flora: 16 - Antonio Giacò; Jacopo Franzoni; Angelino Carta; Diana Cruz-Tejada; Perla Aurora Zanatto; Luca Paino; Emanuele Del Guacchio (Italian Botanist, 2025)
This study presents the first chromosome numbers for Italian populations of two species with a Euro-Mediterranean distribution: Atocion rupestre (L.) Oxelman (Caryophyllaceae) and Mantisalca duriaei (Spach) Briq. & Cavill. (Asteraceae). Both counts confirm the chromosome numbers reported for populations of the same species in other European countries.